Outbreak of Influenza A - H3N2v, in the United States of America, 2022 - Abey Sushan; Shri Vijay Bala Yogendra Shivakumar; Aby Robinson; A Vishnu Kumaran (University of New South Wales, 2023)
This Watching Brief provides analysis of a recent outbreak of Influenza A H3N2v in the United States. The virus is transmitted from pigs to humans, and human to human transmission is rare. There were four confirmed cases in the 2022 flu season, with contact with pigs at swine farms or agricultural fairs.